VD_FINDINFO HC / 2015 / 748 vom 31. August 2015 - VD Tribunal cantonal (2015)
BÉNÉFICE D'INVENTAIRE, INVENTAIRE, DÉCISION D'IRRECEVABILITÉ, CONCLUSIONS | 553 CC, 580 CC, 321 CPC (CH), 117 CDPJ, 118 CDPJ